The effect of face-to-face or group education during pregnancy on sexual function of couples in Isfahan - Parvin Bahadoran; Maryam MohammadiMahdiabadzade; Hamid Nasiri; Ali GholamiDehaghi (Wolters Kluwer Medknow Publications, 2015)
Background: Pregnancy can be in conflict with sexual function which can be affected by physical and psychological changes during pregnancy. Therefore, comparison of the effect of face-to-face education with group education on sexual function during pregnancy in couples was the purpose of this research. Materials and Methods: In this quasi-experimental pre-test post-test study, 64 pregnant couples were selected and randomized in two groups in Isfahan. The data were collected using the triangulation of Female Sexual Function Index (FSFI), Brief form of Sexual Function Inventory (BSFI), and demographic characteristics questionnaires. The data were analyzed by independent t-test, paired t-test, Chi-square, analysis of covariance (ANCOVA), and analysis of variance (ANOVA) in SPSS. Results: No significant difference was found in the demographic characteristics between the two groups. Education was effective on sexual function in the two groups of women (P < 0.001), but no significant difference was found between the two groups (P = 0.61). Also, education was effective on sexual function of men in both the groups (P < 0.001) and there was a significant difference between the two groups (P = 0.003). Meanwhile, there was no significant difference between couples regarding the education (P = 0.104). Conclusions: The results of the study showed that type of education plays a role in improvement of sexual function in pregnancy. In addition, sex education is effective in prevention of sexual disorders in pregnancy. Therefore, having a special approach toward sex education classes during pregnancy is important for the health providers, particularly midwifery professionals.